CRC Handbook of Laboratory Safety, Fifth Edition - Furr, A. Keith (CRC Press, 2009)
Expanded and updated, The CRC Handbook of Laboratory Safety, Fifth Edition provides information on planning and building a facility, developing an organization infrastructure, planning for emergencies and contingencies, choosing the correct equipment, developing operational plans, and meeting regulatory requirements. Still the essential reference tool, the New Edition helps you organize your safety efforts to adhere to the latest regulations and use the newest technology. The ideal reference to OSHA safety standards and government regulations Thoroughly revised, the CRC Handbook of Laboratory Safety, Fifth Edition includes new OSHA laboratory safety standards, the 1994 NRC radiation safety standards, guidelines for X-ray use in hospitals, enforcement of standards for dealing with blood-borne pathogens, OSHA actions covering hazardous waste operations and emergency response, and the latest CDC guidelines for research with microbial hazards. Every word on every page has been scrutinized, and literally hundreds of changes have been made to bring the material up to date. See what's new in the New Edition: